The Effect of High-Definition Transcranial Direct Current Stimulation of the Right Inferior Frontal Gyrus on Empathy in Healthy Individuals - Wu, Xiaoling; Xu, Feifei; Chen, Xingui; Wang, Lu; Huang, Wanling; Wan, Ke; Ji, Gong-Jun; Xiao, Guixian; Xu, Sheng; Yu, Fengqiong; Zhu, Chunyan; Xi, Chunhua; et al. (Frontiers in Human Neuroscience, 2018)
Empathy, including cognitive and emotional empathy, refers to the ability to infer the mental state of others as well as to the capacity to share emotions. The neural mechanisms involved in empathy are complicated and not yet fully clear and previous studies have shown that both cognitive and emotional empathy are closely associated with the inferior frontal gyrus (IFG). In this study, we examined whether empathy could be modulated by high-definition transcranial direct current stimulation (HD-tDCS) of the right IFG. Twenty-three healthy participants took part in all three experimental conditions (i.e., anodal, cathodal, and sham stimulation) in a randomized order. Participants then completed the Chinese version of the Multifaceted Empathy Test which assessed both cognitive and emotional empathy. The results showed that the scores for cognitive empathy following cathodal stimulation were significantly lower than those obtained following sham stimulation. In addition, the scores for cognitive empathy following anodal stimulation were higher than those obtained following sham stimulation, though the difference was only borderline significant. However, the results failed to show that stimulation of the right IFG using HD-tDCS plays a role in emotional empathy. Our results suggest that the right IFG plays a key role in cognitive empathy and indicates that the HD-tDCS can regulate cognitive empathy by inducing excitability changes of the right IFG.